Bimbingan Kelompok dengan Teknik Permainan Tradisional Cublak-Cublak Suweng untuk Meningkatkan Adaptability Skill - Zahro, Indah Fajrotuz (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study aims to determine of group guidance with traditional games cublak-cublak suweng in improving the adaptability skills. This study is a quantitative using a pre-test post-test one group design. Subjek in this study is 6 children and data collectors is guttman scale with 2 alternative answer. The validity of the product moment of 40 items, it is known that 19 items are valid. The reliability test with the Alpha Cronbach obtained a value of 0.750. Data analysis using the Wilcoxon Test shows The Sig value is 0.003 < 0.05 which means there is a difference between the pretest and posttest. In the research results it is known that the post-test results have an increase in value from the pre-test results before being given 6 treatments. This study shows that group guidance with cublak-cublak suweng traditional game techniques as an effort to improve adaptability skills.